LC-MS/MS method for the quantitation of serum tocilizumab in rheumatoid arthritis patients using rapid tryptic digestion without IgG purification - Takashi Mochizuki; Kaito Shibata; Takafumi Naito; Kumiko Shimoyama; Noriyoshi Ogawa; Masato Maekawa; Junichi Kawakami (Elsevier, 2022)
The quantitation of serum tocilizumab using liquid chromatography tandem-mass spectrometry (LC-MS/MS) method has not been widely applied in clinical settings because of its time-consuming and costly sample pretreatments. The present study aimed to develop a validated LC-MS/MS method for detecting serum tocilizumab by utilizing immobilized trypsin without an immunoglobulin G purification step and evaluate its applicability in the treatment of rheumatoid arthritis (RA) patients administered intravenously or subcutaneously with tocilizumab. The tocilizumab-derived signature peptide was deciphered using a nano-LC system coupled to a hybrid quadrupole-orbitrap mass spectrometer. The serum tocilizumab was rapidly digested by immobilized trypsin for 30 min. The chromatographic peak of the signature peptide and that of the internal standard were separated from the serum digests for a total run time of 15 min. The calibration curve of serum tocilizumab concentration was linear with a range of 2-200 μg/mL. The intra- and inter-day accuracy and relative standard deviation (RSD) were 90.7%-109.4% and <10%, respectively. The serum tocilizumab concentrations in the RA patients receiving intravenous and subcutaneous injections were 5.8-28.9 and 2.4-63.5 μg/mL, respectively. The serum tocilizumab concentrations using the current method positively correlated with those using the enzyme-linked immunosorbent assay, although a systematic error was observed between these methods. In conclusion, a validated LC-MS/MS method with minimal sample pretreatments for monitoring serum tocilizumab concentrations in RA patients was developed.